THE DA'WAH METHODOLOGY OF THE PROPHETS ULU AL-'AZMI - Hamdani Hamdani; Zamakhsyari Abdul Majid; Abdul Hamid (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
The Da'wah methodology of the Prophets Ulu Al-'Azmi, distinguished by their steadfast determination and resilience, has served as a model for Prophets and Da’i (Islamic preachers) throughout history. This study aims to introduce and uncover the da'wah approaches, specifically focusing on Prophet Isa AS (Jesus), to provide contemporary da’i with a framework rooted in the Qur'an and Sunnah. The research employs a qualitative library research method, analyzing historical, sociological, and descriptive data derived from the Qur’an, Sunnah, and scholarly works recognized by the Muslim community, including classical and modern historical texts. Data analysis involves triangulating sources, objectives, and references to ensure a scientifically valid and measurable outcome. The findings of the study highlight three main points: First, the Prophets are referred to as Ulu Al-'Azmi because they were divinely chosen for their unwavering determination, patience, and commitment to their mission. Second, the approach and methods of the Ulu Al-'Azmi Prophets are strikingly similar, emphasizing a Rabbaniy (divinely-guided) approach and exemplary moral conduct. Their methods include modeling (Qudwah), wisdom (Hikmah), dialogue, and admonition (Mau'izhah). Third, Prophet Isa AS's approach to da'wah centered on showcasing his prophetic miracles, spiritual journey, and a methodology grounded in compassion, gentleness, and both promises and warnings. His da’wah was tailored to the psychological and social conditions of the Children of Israel at the time.